Targeting BCL11A/nuclear receptor complexes in breast tumour cells using CRISPR-Cas9 genome editing tool - Clemente Olivo, Maria del Pilar (2017)
Many breast cancer patients can respond well to therapies that target Estrogen Receptor, Progesterone Receptor and Human Epidermal Growth Factor 2 (HER-2). However, a proportion of patients (15%) lack expression of these proteins, the so-called triple negative breast cancers (TNBC). TNBC tumours arise from basal cells and have generally poor prognosis, as there are no targeted therapies available. Identifying molecular biomarkers for TNBC tumours will improve diagnosis, treatment and generation of novel targeted therapies. Transcription co-repressor BCL11A, a proto-oncogene in hematopoietic cell malignancies, is also highly expressed in TNBC and it has been shown to be required for TNBC tumour growth. Previous work from our group demonstrated interactions of BCL11A with several orphan Nuclear Receptors expressed in tumours, including NR2E3/PNR. It has been reported that NR2E3/PNR regulates ESR1 (ERalpha) expression in ERalpha-positive cell lines, and recent unpublished data from our group indicates it can heterodimerise with another nuclear receptor, PPARgamma. Therefore, this study investigates the hypothesis that BCL11A/NR2E3 complexes may contribute to repression of ESR1 expression in TNBC tumours. In addition, we wanted to investigate potential interactions of NR2E3/PNR and PPARgamma in breast cancer cells. We employed the CRISPR Cas9 genome editing technique to target the BCL11a, NR2E3/PNR and PPARgamma genes in the TNBC cell line MDA-MB-468. Disruption of these genes in situ would generate useful cell models to study these complexes and their role in gene regulation and tumourigenesis. Although hampered by the poor ability of MDA-MB-468 to propagate from sorted single cell isolates, we present evidence for successful targeting of BCL11A, NR2E3/PNR and PPARgamma genes by CRISPR editing. We also report the derivation of a PPARgamma overexpressing clone of MDA-MB468 that shows increased sensitivity to Rosiglitazone.